A novel 1, 8‐naphthalimide‐based fluorescent chemosensor for the detection of HSA in living cells. Issue 1 (19th December 2022) - Mo, Liuting; He, Wanqi; Tang, Yonghe; Liang, Danlian; Yang, Chan; Lin, Weiying
Abstract: Human serum albumin (HSA) is an essential protein for maintaining human health. Accurate detection and quantification of HSA are of great significance for disease diagnosis and biochemical research. Here, a new HSA fluorescent probe BNPE based on the 1, 8‐naphthalimide fluorophore was designed and synthesized. The probe could recognize HSA through a twisted intramolecular charge transfer mechanism, effectively avoid the interference of most substances, and realize HSA fluorescence imaging in living cells.